Ocean acidification decreases plankton respiration: evidence from a mesocosm experiment ... : تحمض المحيطات يقلل من تنفس العوالق: دليل من تجربة الكون المتوسط ... - Kristian Spilling; Allanah Paul; Niklas Virkkala; Tom Hastings; Silke Lischka; Annegret Stuhr; Rafael Bermúdez; Jan Czerny; Tim Boxhammer; Kai G. Schulz; Andrea Ludwig; Ulf Riebesell (OpenAlex, 2016)
Abstract. Anthropogenic carbon dioxide (CO2) emissions are reducing the pH in the world's oceans. The plankton community is a key component driving biogeochemical fluxes, and the effect of increased CO2 on plankton is critical for understanding the ramifications of ocean acidification on global carbon fluxes. We determined the plankton community composition and measured primary production, respiration rates and carbon export (defined here as carbon sinking out of a shallow, coastal area) during an ocean acidification experiment. Mesocosms ( ∼ 55 m3) were set up in the Baltic Sea with a gradient of CO2 levels initially ranging from ambient ( ∼ 240 µatm), used as control, to high CO2 (up to ∼ 1330 µatm). The phytoplankton community was dominated by dinoflagellates, diatoms, cyanobacteria and chlorophytes, and the zooplankton community by protozoans, heterotrophic dinoflagellates and cladocerans. The plankton community composition was relatively homogenous between treatments. Community respiration rates were ... : الملخص: تعمل انبعاثات ثاني أكسيد الكربون البشرية المنشأ (CO2) على تقليل درجة الحموضة في محيطات العالم. يعد مجتمع العوالق مكونًا رئيسيًا يقود التدفقات الكيميائية الحيوية، وتأثير زيادة ثاني أكسيد الكربون على العوالق أمر بالغ الأهمية لفهم تداعيات تحمض المحيطات على تدفقات الكربون العالمية. حددنا تكوين مجتمع العوالق وقمنا بقياس الإنتاج الأولي ومعدلات التنفس وتصدير الكربون (المحدد هنا على أنه غرق الكربون من منطقة ساحلية ضحلة) أثناء تجربة تحمض المحيطات. تم إنشاء Mesocosms (55 متر مكعب) في بحر البلطيق مع تدرج مستويات ثاني أكسيد الكربون التي تتراوح في البداية من المحيط (240 ميكرومتر)، وتستخدم كعنصر تحكم، إلى ثاني أكسيد الكربون العالي (حتى 1330 ميكرومتر). كان مجتمع العوالق النباتية تهيمن عليه السوطيات الثنائية والدياتومات والبكتيريا الزرقاء والكلوروفات، وكان مجتمع العوالق الحيوانية تهيمن عليه السوطيات الأولية والسوطيات الثنائية غير المتجانسة والكلدوكيرات. كان تكوين مجتمع العوالق متجانسًا نسبيًا بين العلاجات. كانت معدلات التنفس في المجتمع أقل عند مستويات عالية من ثاني أكسيد الكربون. كان التنفس المعادِل للكربون أقل ...